Effect of Contact Time and Stirring Speed on Biosorption of Lead (II) Using Sugarcane Bagasse - Pasaribu, Nur Rizky; Kurniawati, Desy (Indonesian Journal of Chemical Science and Technology (IJCST), 2024)
Lead is a hazardous and toxic metal if it reaches human organs in sufficient doses or if it is present in water. Pb2+ can build up in the brain, causing cancer, disorders of nerve cells, kidneys and mental health as well as problems with male reproduction and resulting in bone irregularities in children. As a result, it is vital to regulate the presence of this metal in water. Biosorption is a heavy metal removal technique that use biomass as an adsorbent. The biosorption method was conducted in this study employing sugarcane bagasse as an adsorbent and batch contacting. Variations in contact duration and stirring speed were tested in this study to determine the influence of contact time and stirring speed on the biosorption process. The study's findings revealed that a contact duration of 60 minutes and a stirring speed of 100 rpm were the best conditions in this research.